Modele kryzysów walutowych - Banasiak, Katarzyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The article describes and characterizes the models of currency crises. The presentation of the first-generation model is based on the crisis in Latin America, the second-generation model based on the crisis of European Monetary System and the Asian crisis exemplifi es the third-generation model. The article demonstrates a non-zero-sum game which displays the role of the currency reserves. It is shown that the level of the currency reserves has an impast on both the probability of potential speculative attack and the investors’ way of thinking, as well as their investment strategies.